2021
DOI: 10.3389/fevo.2021.759732
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Responses of Sargassum muticum, a Potential Golden Tide Species, to Different Levels of Light and Nitrogen

Abstract: Sargassum golden tides have bloomed frequently in many sea areas throughout the world, and negatively impacted on the local marine ecology. Sargassum muticum commonly inhabits rocky shores. It is now distributed worldwide due to its invasiveness, and recently drifting individuals have been observed on the coasts of Canary Islands. However, as a potential golden tide alga, physiological, and ecological studies of this species have not been frequently explored. To investigate the responses of S. muticum to light… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Nevertheless, the responses to light changes found in this study were similar to those observed in other algae, including benthic Sargassum species and the few data published on holopelagic species. For example, in S. muticum and S. henslowianum, increases in P max and respiration rates and a decrease in pigment content have been reported at increasing irradiances (Zou et al 2018;Yan et al 2021). P max and respiration rates obtained in S. fluitans and S. natans I at LL had similar ranges to those of tropical shallow macrophytes, but were much lower than those of the highly productive temperate M. pyrifera (Chisholm 2003;Colombo-Pallotta et al 2006;Meyer et al 2016;V asquez-Elizondo & Enríquez 2016).…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…Nevertheless, the responses to light changes found in this study were similar to those observed in other algae, including benthic Sargassum species and the few data published on holopelagic species. For example, in S. muticum and S. henslowianum, increases in P max and respiration rates and a decrease in pigment content have been reported at increasing irradiances (Zou et al 2018;Yan et al 2021). P max and respiration rates obtained in S. fluitans and S. natans I at LL had similar ranges to those of tropical shallow macrophytes, but were much lower than those of the highly productive temperate M. pyrifera (Chisholm 2003;Colombo-Pallotta et al 2006;Meyer et al 2016;V asquez-Elizondo & Enríquez 2016).…”
Section: Discussionmentioning
confidence: 85%
“…Under LL, S. fluitans and S. natans I had high Chl a content, comparable to that of the subtidal Macrocystis pyrifera (Colombo-Pallotta et al 2006), whereas the Chl c content was much higher in S. fluitans than in S. natans I, increasing absorption and allowing higher α. In contrast, HL reduced the pigment content, probably as a strategy to change the size and number of PSUs and/or the ratio of PSII to PSI to avoid excess light (Kirk 2011;Yan et al 2021). According to these observations, P max and respiration were low at LL and increased under HL in both holopelagic species.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations